Functional MRI Examination of Visual Pathways in Patients with Unilateral Optic Neuritis. (17th July 2012) - Mascioli, Giulia; Salvolini, Simone; Cavola, Gian Luca; Fabri, Mara; Giovannini, Alfonso; Mariotti, Cesare; Salvolini, Luca; Polonara, Gabriele
Abstract : The relations between brain areas involved in vision were explored in 8 patients with unilateral acute optic neuritis using functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI). In all patients monocular stimulation of affected and unaffected eye elicited significantly different activation foci in the primary visual cortex (V1), whereas the foci evoked in the middle temporal visual area (area V5) were similar in size and in delay of blood-oxygen-level-dependent response. DTI analysis documented lower white matter anisotropy values and reduced fibre reconstruction in the affected compared with the unaffected optic nerves. The preserved activation of area V5 observed in all our patients is an interesting finding that suggests the notion of a different sensitivity of the optic pathways to inflammatory changes.